1998
DOI: 10.2135/cropsci1998.0011183x003800030037x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Disease Resistance Loci in Barley on the Basis of Visual Assessment of Naturally Occurring Symptoms

Abstract: Using field-scored data of disease severity under natural infestation, we mapped loci affecting resistance to powdery mildew (Blumeria graminis DC f. sp. hordei ~m. Marchal), leaf rust (Puccinia hordei Otth.), stem rust (Puccinia graminis f. sp. tritici Eriks. & E. Henn.), scald [Rhynchosporium secalis (Oudem.) J.J. Davis], and net blotch (Pyrenophora teres Drechs.). The mapping population included parents and doubled-haploid progeny of the two-row barley cross Harrington/TR306. Resistance was affected by two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 1 publication
6
47
1
Order By: Relevance
“…It occurred in the 'Igri' × 'Danilo' cross (Backes et al, 1995), and in the Harrington × TR306 cross (Spaner et al, 1998). In conclusion, all the QTLs for PR against scald detected in the present L94 × 'Vada' cross are supported by previously mapped QTLs in various barley populations.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…It occurred in the 'Igri' × 'Danilo' cross (Backes et al, 1995), and in the Harrington × TR306 cross (Spaner et al, 1998). In conclusion, all the QTLs for PR against scald detected in the present L94 × 'Vada' cross are supported by previously mapped QTLs in various barley populations.…”
Section: Discussionsupporting
confidence: 80%
“…The fact that they were detected in both years lends confidence to the reliability of these QTLs. The other QTL, Rbgq3, mapped at 130 cM from the tip of the short arm on chromosome 7 (5H) and is at a similar position as a QTL reported by Spaner et al (1998) andby Saghai Maroof et al (1994). It is possible that some other QTLs for powdery mildew resistance with smaller effects were not identified due to the small population size (51 RILs) and the low level of infection and, as a consequence, the modest contrast in infection severity between the RILs.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…spontaneum Rrs12 on 7HS, Rrs13 on 6HS, Rrs14 on 1HS, and Rrs15 on 7HL (Abbott et al 1992;Abbott et al 1995;Garvin et al 1997;Garvin et al 2000;Genger et al 2003a;Genger et al 2003b;Genger et al 2005), or from Hordeum bulbosum Rrs16 on 4HS (Pickering et al 2006). Furthermore, a number of QTL studies revealed QTLs for scald resistance on several chromosomes whose loci often coincided with locations of known scald resistance genes (Backes et al 1995;Bjørnstad et al 2004;Cheong et al 2006;Genger et al 2003;Grønnerød et al 2002;Spaner et al 1998;Thomas et al 1995;von Korff et al 2005;Wagner et al 2008;Yun et al 2005).…”
Section: Introductionmentioning
confidence: 99%